Language Practices in Multilingual Ghanaian Nuclear Families: Exploring Mother-Child Interaction and L1 Transmission - Lawer, Richard Ayertey (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
Ghana is a country with about 79 indigenous languages. Some of these languages have become endangered through the phenomenon of language shift. This study explored the multilingual situation of homes of Ghanaian nuclear families, seeking to understand how the language practices of nuclear families impact language endangerment in the country. The study employed a qualitative approach to analyze two nuclear families as a sociolinguistic domain where members of the families make choices regarding language use and practices. Data for the study were obtained via participant observation of two nuclear families and interviews with the spouses of both families. The findings showed that in multilingual families, the language the children acquire as their L1 is often the language of mother-child interaction. The study showed further that fathers' L1 becomes endangered when that is not the language of interaction between mother and children. The findings revealed that even though parents wish to preserve their L1 and culture by passing on their L1 to their children, this goal becomes threatened when their L1 is not the language of mother-child interaction in the home. The findings reinforce the idea that language maintenance is not just an individual choice but broader sociolinguistic and cultural forces shape it. The endangered status of the parents' L1 in nuclear families demonstrates how family language policies, gendered linguistic roles, and societal pressure interact in influencing language endangerment. The study recommended that parents need to put in the effort to ensure that their L1 is used at home to help their children develop competence in it.